QUR'ANIC MANUSCRIPTS OF TERENGGANU AND ACEH (CODICOLOGICAL ANALYSIS OF QUR'ANIC MANUSCRIPTS A47 AND A694 FROM THE PNRI COLLECTION) - Setiawan, Budi; Herman, Herman; Saleh, Putri M; Billah, Muhammad Qudwah I’tishom (Jurnal Al-Ijtimaiyyah, 2026)
This study examines the codicological characteristics of two ancient Qur'anic manuscripts, A47 from Terengganu and A694 from Aceh, which are part of the collection of the National Library of the Republic of Indonesia (PNRI). Using a qualitative approach with descriptive-analytical methods, this research analyzes the physical aspects of the manuscripts including calligraphy, illumination, paper type, binding techniques, and additional texts, as well as textual aspects covering rasm, qira'at, dhabt, tajwid, and waqf signs. The results show that both manuscripts reflect a unique synthesis between Islamic traditions and local cultures. Manuscript A47 displays complex geometric patterns with gold color dominance, reflecting the aesthetics of Terengganu, while A694 shows minimalist floral illuminations with dominant red and black colors, characteristic of Acehnese culture. Textual analysis reveals variations in rasm and qira'at, with A694 tending to be more conservative in Rasm Uthmani and following certain qira'at such as Ibn Amir and Hamzah, while A47 is more accommodative to isbat alif and follows the majority qira'at of 'Asim via Hafs. This study concludes that these manuscripts are not only religious texts but also cultural artifacts that reflect the dynamics of transmission and adaptation of the Qur'anic text according to the needs of Muslim communities in Terengganu and Aceh, as well as contributing to the understanding of the history of Islamic civilization in the Archipelago.